OpenGL ir DirectX technologijų spartos palyginimas programuojant trimačius vaizdus - Filatovas, Ernestas; Melničenko, Grigorijus; Jakštys, Vytautas (Information & Media, 2013)
Pagrindiniai trimačių vaizdų apdorojimo konkurentai yra DirectX ir OpenGL technologijos. Straipsnyje pateikiama šių technologijų lyginamoji analizė. Eksperimentiškai tiriama DirectX ir OpenGL technologijų veikimo sparta. Eksperimentams skirta testinė programinė įranga sukurta populiariausiomis programavimo kalbomis C++ ir C#. Darbe pateikiami ir analizuojami tyrimų rezultatai, gauti atlikus kelis skirtingus spartos testus naudojant sukurtą programinę įrangą. Comparison of OpenGL and DirectX technologies in 3D programming Ernestas Filatovas, Grigorijus Melničenko, Vytautas Jakštys Summary In this study, three-dimensional rendering technologies DirectX and OpenGL were reviewed. A comprehensive survey, evaluation of advantages and disadvantages, and a comparative analysis of these technologies have been made. By applying C# and C++ programming languages, the software has been developed for testing the speed of DirectX and OpenGL technologies. A relatively large number of experiments were conducted in order to determine the speed of these technologies. The experiments included visualization of basic and complex shapes movements, and different depth of shapes. The experimental investigations were performed in Windows and they have revealed that the speed of the DirectX technology is higher. This factor is the most signifi cant one in three-dimensional rendering, especially in the development of computer games. The DirectX technology was proved to be fastest while programming in C#. Moreover, the experimental investigations have indicated that the DirectX technology uses CPU resources more effi ciently. e="font-size: 11pt; line-height: 115%; font-family: Calibri, sans-serif;">